2013
DOI: 10.1007/s00221-013-3459-7
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics fingerprints of leader and follower role-taking during cooperative joint actions

Abstract: Performing online complementary motor adjustments is quintessential to joint actions since it allows interacting people to coordinate efficiently and achieve a common goal. We sought to determine whether, during dyadic interactions, signaling strategies and simulative processes are differentially implemented on the basis of the interactional role played by each partner. To this aim, we recorded the kinematics of the right hand of pairs of individuals who were asked to grasp as synchronously as possible a bottl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
151
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(199 citation statements)
references
References 61 publications
28
151
4
1
Order By: Relevance
“…Leader-follower dynamics have been investigated in behavioural studies before (Noy et al, 2011, Sacheli et al, 2013, Wing et al, 2014, and previous work on agency has addressed the roles of imitators (i.e. followers) and initiators (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leader-follower dynamics have been investigated in behavioural studies before (Noy et al, 2011, Sacheli et al, 2013, Wing et al, 2014, and previous work on agency has addressed the roles of imitators (i.e. followers) and initiators (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that both symmetrical and complementary motor adaptation of interacting partners is used when working toward a common goal (Kokal et al, 2009, Masumoto and Inui, 2013, Sacheli et al, 2013. However, the neural mechanisms underlying interpersonal real-time coordination remain largely unknown, as the methodological frameworks to study them have been underdeveloped Roepstorff, 2012, Hari et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This model M6 takes into account the value of the variable A t at the same trial t of L t (table 2). Results showed no significant main effect of baseline session (baseline1 versus baseline2) [F (1,14) ¼ 1.130, p ¼ 0.306], indicating participants achieved the same level of performance in baseline1 and baseline2. Thus, we averaged the two sessions and used their mean to normalize (i.e.…”
Section: Model Analysesmentioning
confidence: 99%
“…This analysis showed a main effect of test session [F (1,14) Given our specific hypotheses of signalling and imitation regarded the comparison between test1 and test2, the kinematic analyses were performed only on these two sessions. Table 1.…”
Section: Test1/2mentioning
confidence: 99%
See 1 more Smart Citation